Cats-Behavior Model Illustrating the Servqual of Public Service Delivery in Nepalese Context - Palikhe, Amin (Kalika Journal of Multidisciplinary Studies, 2024)
There are numerous models of quality service delivery that are now in use, highlighted on SERVQUAL dimensions that measures quality of service offered by various social or nonprofit and profit oriented organization. The purpose of this article is to develop a typologically modified model for measuring the quality of services deliver in Nepalese context. Therefore, typological modification methodological approach has been used to conceptualize the SERVQUAL model to CATS-Behavior model. In order to assure appropriate, efficient, and effective service delivery, this study develops a typologically modified model of service quality dimensions that illustrates and ensures quality service delivery. In conclusion, because the document is conceptual in nature, it can be used by practitioners, researchers, academics, and public officials in place of providing and measuring quality of services delivery in Nepalese context.